2014
DOI: 10.1007/s11340-014-9939-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Measurements of Residual Stresses Caused by Severe Thermomechanical Deformation during FSW

Abstract: In engineering processes, residual stresses can be intense once high plastic deformation and temperature gradient are involved. This is exactly the case for friction stir welding (FSW) in which both rotational and translational movements of the tool induce extreme temperature gradient and plastic deformation. In this research, the extents of longitudinal and transverse residual stresses are measured within the AA7075-T6 plates welded through FSW process using ultrasonic method. According to the obtained result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This article is not to scrutinize the technical jargon of the ultrasonic RS measurement and the corresponding details can be found in Papahn et al. 12 Briefly, all the ultrasonic waves are converted to longitudinal and transverse waves upon contacting a surface. In this article, a wave transmitter and a receiver have been installed based on two hoofs under the angle of 50° relative to the specimen surface (Figure 8).…”
Section: Rs Measurement and Temperature Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article is not to scrutinize the technical jargon of the ultrasonic RS measurement and the corresponding details can be found in Papahn et al. 12 Briefly, all the ultrasonic waves are converted to longitudinal and transverse waves upon contacting a surface. In this article, a wave transmitter and a receiver have been installed based on two hoofs under the angle of 50° relative to the specimen surface (Figure 8).…”
Section: Rs Measurement and Temperature Acquisitionmentioning
confidence: 99%
“…Moreover, they reported that the stresses are tensile in weld region, while it is compressive beyond this region, which causes bending moment around the longitudinal axis and corresponding plate distortion. Finally, the authors 12 employed the ultrasonic method to measure the RS induced by in-air FSW process and demonstrated that the longitudinal RS is almost three times greater than the transverse one after FSW process. Furthermore, they recommended using the ultrasonic method for studying on the joints fabricated by FSW due to its proposed advantages including low cost involved and portability of the needed measurement equipment In addition to experimental studies, some models are also proposed to numerically estimate the RS caused by FSW to avoid the high cost involved in experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In order to measure the axial and translational forces as well as the temperature rise, a fixture with a special design is utilized [17], which is illustrated in Fig. 2.…”
Section: Experimental Procedures and Theorymentioning
confidence: 99%
“…For instance, Hughes and Kelly [19] specified that the error of this method does not exceed over 4 %. Furthermore, H. Papahn et al [17] showed that the ultrasonic method may result in some errors caused by the calibration test, the non-smooth surface of the workpiece, heterogeneity of the micro-texture and the flaws created throughout the welding process. Figure 3 schematically represents the experimental setup of ultrasonic test to extract the RS, in which a 12.5-MHz normal probe is used for determination of LCR waves.…”
Section: Experimental Procedures and Theorymentioning
confidence: 99%
“…There are several nondestructive techniques that are usually applied in engineering practice to evaluate structure stress, such as neutron-diffraction (ND) [4][5] , X-ray diffraction (XRD) [6][7] and ultrasonic testing (UT) [8][9] , etc. Comparing with other methods, the ultrasonic method is acknowledged to be one of the most potential non-destructive inspection methods in structural stress measurement filed for its fine sensitivity, veracity and good operation features.…”
Section: Introductionmentioning
confidence: 99%